Human-AI Resilience in Project Management: A Framework For Post-Ai Digital Transformation - Jiomarie Jesus; Joeriz B. Arnejo; Danilo Y. Patalinghug; Jovert J. Delegencia; Bridgette Baguio Mananghac (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
Integrating artificial intelligence (AI) into large-scale digital transformation has shifted project management from process-centric models to adaptive, human-centered frameworks. This study addressed a critical gap in the literature by introducing the Human-AI Resilience Framework (HARF), which emphasizes emotional safety, resilience, and ethical adaptation in AI-driven environments. Employing a convergent mixed-methods design, the study surveyed 400 project managers and conducted thematic interviews with 50 AI-experienced leaders accross Asia-Pacific region. Quantitative analysis, including ANOVA and Structural Equation Modelling (SEM), validated HARF by revealing strong associations between human resilience and project success (B=0.48, p<0.001). Emotional burnout significantly varied accross industries, with the IT and healthcare sectors reporting the highest levels. Thematic analysis revealed six core themes, such as AI-augmented leadership and psychological safety, highlighting the centrality of human agency in AI integration. HARF distinguished itself by aligning technological capabilities with emotional intelligence, offering a multidimensional perspective on digital governance. It provided actionable strategies for mitigating burnout, fostering ethical AI onboarding, and strengthening team cohesion. As AI reshaped the modern workplace, HARF delivered a practical, evidence-based roadmap for project leaders striving to balance algorithmic precision with human insight. The framework ultimately redefined project success through the lens of human-AI synergy, offering critical value for navigating complex digital ecosystems.